A Reconsideration of the Sugar Sweetened Beverage Tax in a Household Production Model - Di Xiang; Lue Zhan; Massimo Bordignon (Center for Economic Studies and ifo Institute (CESifo), 2018)
We study the impact of a hypothetical tax on sugar - sweetened beverages (SSBs) on the US households' nutrients purchase, welfare change, and health benefit. Differently from the traditional approach, Food at Home(FAH) is here defined as a “home” good instead than a market good and consumers' demands derived under the assumption that households maximize utility subject to both a money and a time constraint. The model is estimated by using an incomplete approximate Exact Affine Stone Index (EASI) demand system on a data set built by merging the most recent waves of the US consumer expenditure and time use surveys. Results show that a SSB tax would be much more effective in decreasing household nutrients purchase than it would appear by estimating a model neglecting time costs in home food production. A tax induced increased in SSB price by 20% is predicted to decrease the per capita energy purchase by 29.17 kcal/day. The annual health benefits of the tax, measured only in terms of reduced household medical expenditure, would overcome estimated welfare losses by more than 400 million.
Keywords: D12; D13; I18; 330; sugar-sweetened beverage tax; obesity; household production